Luz intensa pulsada e ácido 5 aminolevulínico no tratamento de queratoses actínicas e fotoenvelhecimento facial - Haddad, Alessandra [UNIFESP] (2010)
BACKGROUND: Photodynamic rejuvenation is the term used to the treatment of actinic keratosis and photodamage with photodynamic therapy. OBJECTIVE: Evaluate the efficacy of photodynamic therapy with aminolevulinic acid and intense pulsed light in the treatment of actinic keratosis and photodamage. METHODS: Fourty three patients mean age 71,3 years, were randomized in three groups: Control (IPL 18J); Treatment I (ALA+ IPL 16J); and Treatment II ( ALA+ IPL 18J) and evaluated clinically an photographically by two observers in Pre, 48hs, 8 weeks and 12 weeks Post-Treatment using Griffth’s Photonumeric Scale. Five actinic keratosis were marked as target in Pre-Treatment and biopsies Pre and Post-Treatment were done in one lesion to evaluate atypias and loss of cellular polarity. RESULTS: Non parametric tests showed marked improvement in mottled pigmentation, texture fine wrinkles in Groups Treatment I and II. In Control Group improvement only in mottled pigmentation. Actinic Keratosis clearance in Groups Treatment I and II were 51,2% and 68,4% respectively, whereas in Group Control it was 5%. In relation to Control Group, Groups Treatment I and II showed significant reduction of atypias and improvement in loss of cellular polarity. CONCLUSIONS: Photodynamic therapy with aminolevulinic acid and intense pulsed light is effective in the treatment of photodamage and actinic keratosis. The resolution of actinic keratosis was better with higher levels of energy.